Pengaruh Program "Yuk Nabung Saham" Terhadap Minat Investasi Pada Kelompok UKM di Kota Prabumulih Sumatera Selatan - Zakaria Harahap (COSTING : Journal of Economic, Business and Accounting, 2020)
Let's Save Stocks Against Investment Interest in SMEs Group in Prabumulih City, South Sumatra. The purpose of this study is to analyze the impact of the "Yuk Nabung Saham" program on investment interest in the SME group in Prabumulih City, South Sumatra. The research method used in this study using a survey method. By collecting primary data and secondary data. The selection of the research location was determined deliberately (purposive sampling) then the data obtained would be analyzed using the T test with simple linear regression. The population selection in this study was the UKM group in Prabumulih as many as 5,436 UKM, the method of determining the sample used was purposive sampling with the consideration of respondents who were influencers / deciders, with sampling using the Slovin Umar formula (2013), so the sample to be used in this study is as many as 98 respondents representing a randomly selected population. The results show that the value of the correlation coefficient and the coefficient of determination can be used to determine the proportion of the independent variables (X) in explaining the Y variable.The correlation coefficient of 0.827 indicates that there is a strong and unidirectional influence between saving stocks and investment interest in the Prabumulih City UKM group. . The coefficient of determination is 0.827 or 82.7%, the variation of saving stocks, which can explain the investment interest variable, while the remaining 13.7% is explained by other variables not examined in this study. Keywords: Saving Stocks and Investment Interest